2015
DOI: 10.11648/j.ijnfs.20150404.19
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment of Carbon Monoxide and Chitosan Reduced Peach Fruit Browning and Softening During Cold Storage

Abstract: Abstract:The effects of postharvest application of chitosan and carbon monoxide (CO) on fruit browning and softening during cold storage (8 ℃) were evaluated. CO (10 µmol/L) significantly delayed the internal browning of peach fruit, and the effect was enhanced in combination with chitosan (1%, w/w). Further studies showed that treatment with CO and chitosan reduced the increase of PPO and POD activities, maintained PAL activity and total phenoilics content at a higher level. Moreover, it also reduced fruit ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Determining the BI is a practical method to evaluate internal browning, which is attributed to the oxidation of phenolic compounds by PPO and POD [38]. These enzymes oxidize phenolic compounds to quinone and quinine-like compounds that produce polymerized brown pigments [6,39]. In the current study, the results showed that 15 mM proline and 0.4% L-cysteine treated peach fruits exhibited lower internal browning in comparison to control fruits during cold storage.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Determining the BI is a practical method to evaluate internal browning, which is attributed to the oxidation of phenolic compounds by PPO and POD [38]. These enzymes oxidize phenolic compounds to quinone and quinine-like compounds that produce polymerized brown pigments [6,39]. In the current study, the results showed that 15 mM proline and 0.4% L-cysteine treated peach fruits exhibited lower internal browning in comparison to control fruits during cold storage.…”
Section: Discussionmentioning
confidence: 54%
“…Internal browning is one of the main disorders of peach fruits during storage life, which appears after long-term storage at low temperatures [5,6]. Determining the BI is a practical method to evaluate internal browning, which is attributed to the oxidation of phenolic compounds by PPO and POD [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation